Ménétrier disease and gastrointestinal stromal tumors: hyperproliferative disorders of the stomach - Robert J. Coffey; Mary Kay Washington; Christopher L. Corless; Michael C. Heinrich (The Journal of Clinical Investigation, 2007)
Ménétrier disease and gastrointestinal stromal tumors (GISTs) are hyperproliferative disorders of the stomach caused by dysregulated receptor tyrosine kinases (RTKs). In Ménétrier disease, overexpression of TGF-α, a ligand for the RTK EGFR, results in selective expansion of surface mucous cells in the body and fundus of the stomach. In GISTs, somatic mutations of the genes encoding the RTK KIT (or PDGFRA in a minority of cases) result in constitutive kinase activity and neoplastic transformation of gut pacemaker cells (interstitial cells of Cajal). On the basis of the involvement of these RTKs in the pathogenesis of these disorders, Ménétrier disease patients have been effectively treated with a blocking monoclonal antibody specific for EGFR and GIST patients with KIT and PDGFRA tyrosine kinase inhibitors.